Creative Economy Development Strategy in an Effort to Increase Income in SMES (UMKM) CV. Cita Mandiri Keripik, Batu City - Maria Yurina Luruk; Nur Ida Iriani; Yuni Setyowati (International Journal of Management and Business, 2025)
The objective of this study is to identify the creative economy development strategy aimed at increasing income in CV SMEs Cita Mandiri Chips Batu City. This research employs a qualitative approach, utilizing data collected through interviews with the leader of CV SMEs Cita Mandiri Chips Batu City. The data analysis methods applied in this study include descriptive analysis and SWOT analysis. The results of the SWOT analysis confirm that the creative economy development strategy to increase the income of CV SMEs Cita Mandiri Chips Batu City includes maintaining product prices in line with the market, ensuring employees adhere to Standard Operating Procedures (SOPs), preserving product quality, offering a variety of products, increasing employee salaries, producing goods based on market demand, stocking non-perishable raw materials, selling products online, maintaining cleanliness and order in product displays at the store, providing bonuses for employees who meet work targets, and utilizing machines for production. The opportunity factors in enhancing the development of the creative economy include a strategic business location near the market, products that serve as souvenir snacks, distinctive product characteristics, and the use of online marketing. Meanwhile, the challenge factors involve the presence of numerous similar businesses in the area, the seasonal availability of fruit raw materials, and rising raw material costs.